ANALISIS PRODUK, MEREK, IKLAN DAN HARGA YANG MEMPENGARUHI MINAT BELI KONSUMEN PADA sim card IM3 (Study Pada Masyarakat Kecamatan Ngaliyan, Kota Semarang) - Himawan Intrada, 06.05.51.0085; Sutino, Sutino (Students Journal of Economic and Management, 2013)
Along with the rapid progress in the world of science and technology, telecommunications are also progressing quite rapidly. Communication is an important issue that is considered capable of helping human life. Since the discovery of means of communication, movement of human life to be changed more easily and feels close. The longer the consumer mindset change with the changing times. Consumers who used to only use communication tool, called the phone, are now beginning to switch to using a cell phone, so the companys telecom service providers can take the new opportunities of the desires and needs of consumers unmet telecommunications technology options that can be utilized by the public each each has advantages and disadvantages. One of these mobile phones based on GSM technologyKey words : Product, brand, advetising, price effect on buying interest